Simultaneous production of carotenoids and chemical building blocks precursors from chlorophyta microalgae. (May 2022) - Rengel, Rocío; Giraldez, Inmaculada; Díaz, Manuel J.; García, Trinidad; Vigara, Javier; León, Rosa
Highlights: Microalgae can be utilized as feedstock for platform chemicals. Co-production of carotenoids can make profitable the generation of HMF and LA. Natural Carotenoids are increasingly-demanded high-value compounds. 5′-hydroxymethylfurfural and levulinic acid were synthesized via starch hydrolysis. Operational conditions were optimized performing Multiple Regression Analysis. Abstract: Replacement of fossil fuels has to be accompanied by the incorporation of bio-based procedures for the production of fine chemicals. With this aim, the microalga Chlamydomonas reinhardtii was selected for its ability to accumulate starch, an environmentally-friendly alternative source of chemical building blocks, such as 5′-hydroxymethylfurfural or levulinic acid. The content of appreciated lipophilic coproducts was assessed in the selected microalga cultured at different nutritional conditions; and the parameters for the acidic hydrolysis of the algal biomass, obtained after pigments extraction, were optimized using a Central Composite Design. Response Surface Methodology predicted that the optimal hydrolysis conditions were elevated temperature, high DMSO % and short hydrolysis time for glucose. LA was favored at long times and high acid % and 5′-HMF at lower acid % and high DMSO %. Chlamydomonas can therefore be used as a sustainable feedstock for the simultaneous production of high-added value lipophilic compounds and platform chemicals.